2020
DOI: 10.1038/s41467-020-17401-3
|View full text |Cite|
|
Sign up to set email alerts
|

Orexin signaling modulates synchronized excitation in the sublaterodorsal tegmental nucleus to stabilize REM sleep

Abstract: The relationship between orexin/hypocretin and rapid eye movement (REM) sleep remains elusive. Here, we find that a proportion of orexin neurons project to the sublaterodorsal tegmental nucleus (SLD) and exhibit REM sleep-related activation. In SLD, orexin directly excites orexin receptor-positive neurons (occupying ~3/4 of total-population) and increases gap junction conductance among neurons. Their interaction spreads the orexin-elicited partial-excitation to activate SLD network globally. Besides, the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 68 publications
(125 reference statements)
3
46
0
Order By: Relevance
“…Alternatively, children with migraine may be biologically sleepier than their healthy counterparts. This is at odds with findings from actigraphy 42 and questionnaire-based studies 43 in pediatric migraine patients which found longer SOL in patients compared to healthy controls. Although, actigraphy and self-report data are less accurate than PSG, particularly for SOL 44 .…”
Section: Polysomnography -Childrenmentioning
confidence: 78%
See 1 more Smart Citation
“…Alternatively, children with migraine may be biologically sleepier than their healthy counterparts. This is at odds with findings from actigraphy 42 and questionnaire-based studies 43 in pediatric migraine patients which found longer SOL in patients compared to healthy controls. Although, actigraphy and self-report data are less accurate than PSG, particularly for SOL 44 .…”
Section: Polysomnography -Childrenmentioning
confidence: 78%
“… 39 Furthermore, cutaneous allodynia, a prominent symptom during migraine attacks, has been shown to worsen in response to REM sleep deprivation, 3 thus indicating potential dysfunction in mechanisms underlying REM-NREM or REM-wake transitions in migraine. A plausible neural correlate for this is the hypothalamic orexinergic system, which plays a critical role in stabilizing sleep/wake transitions and REM sleep, 40 and is linked to migraine, suggesting multiple points of intersection between sleep and trigeminal pain. This is speculative, and the relationship with REM sleep is likely to be complex.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sleep impairments such as insomnia, fragmented sleep and narcolepsy are common in PD patients [ 83 ]. The orexins play a major role in the regulation of sleep [ 84 ] and thus it is not surprising that orexin system dysregulation results in various sleep impairments, including destabilization and loss of REM sleep [ 34 , 85 , 86 ], more sleep to wake transitions [ 26 ], and sleep fragmentation [ 87 ]. Perhaps the most interesting link between the orexin system and PD is narcolepsy, which is commonly experienced by PD patients [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a potential dysfunction in mechanisms underlying REM-NREM or REM-wake transitions in migraineurs. A plausible neural correlate for this is the hypothalamic orexinergic system which plays a critical role in stabilizing sleep/wake transitions and REM sleep 34 , and has been linked to migraine, suggesting multiple points of intersection between sleep and trigeminal pain. Although, this is speculative, and the relationship with REM sleep is likely to be complex and bi-directional.…”
Section: Discussionmentioning
confidence: 99%